Radionecrosis of the larynx: concerns regarding surgery and reconstruction - Youssef, Ahmed; Zahran, Mohamed; Lynnhtun, Kyaw; Morsy, Mohamed; Domin, Ahmed; Bhatia, Daman; Cope, Daron; Eisenberg, Robert (Australian Journal of Otolaryngology; Vol 2 (March 2019): Australian Journal of Otolaryngology, 2019)
Background: Laryngeal cancer represents one of the most common head and neck malignancies, accounting for 20% of all cases. The vast majority of tumors are squamous cell carcinomas. Radiotherapy is a primary or adjuvant therapy in the control and treatment of head and neck malignancies. Immediate and late complications in the head and neck region include soft-tissue necrosis, xerostomia, mucositis, osteoradionecrosis and chondroradionecrosis. This study aims to illustrate the possibility of laryngeal chondroradionecrosis as an infrequent complication of conventional radiotherapy and assess the state of art for management of this sequelae. Methods: We are presenting a case series of three patients who had received radiotherapy as a primary treatment for laryngeal cancer of different TNM stages. They were later presented with grade 3–4 chondroradionecrosis. Results: Salvage laryngectomy was performed in all patients with addition of pectoralis major myocutaneous or myofascial flap for reconstruction. Conclusions: Chondroradionecrosis of larynx is an uncommon but a serious complication of radiotherapy. Salvage resection and reconstruction using pedicled flaps such as the pectoralis major myocutaneous flap is the standard treatment for these critical patients.